The The Effect Of Mosquito Larvae Monitoring Training On Knowledge And Skills In Efforts To Prevent Dengue Fever At SDN 2 Sukun, Malang City - Agustiningsih, Resa Elok; Pudji Suryani; Fiashriel Lundy (Jurnal Kesehatan Masyarakat Celebes, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia, especially in endemic areas. Active participation of elementary school students through training as larvae monitors is a key strategy. Objectives: To determine the effect of larvae monitor training on knowledge and skills in preventing DHF among fifth-grade students at SDN 2 Sukun Malang. Research Metodes: A pre-experimental study with a onegroup pretest-posttest design was conducted involving 30 purposively selected fifth-grade students. A questionnaire and observation checklist were used, analyzed using paired t-test. Results: There was a significant increase in knowledge (p < 0.05) and skills (p < 0.05) after the larvae monitor training was conducted. Conclusion : The study concludes that larvae monitor training is effective in improving students' knowledge and skills in preventing DHF. The involvement of students as larvae monitoring cadres is expected to become a sustainable promotive and preventive strategy in the school environment.Keywords: larvae monitor; training; knowledge; skills; dengue